The complete mitochondrial genome of Schizothorax chongi (Fang, 1936) (Teleostei, Cyprinidae, Schizothoracinae). (3rd March 2016) - Que, Yan-Fu; Xu, Dong-Mei; Li, Wei-Tao; Yang, Zhi; Tang, Hui-Yuan; Shao, Ke
Abstract: Schizothorax chongi is an endemic and important polyploidy fish in the upper stream of the Yangtze River. S. chongi represents a typical model species to study historical adaptation and evolution in the Tibetan Plateau. In this study, the complete mitochondrial DNA genome sequence of S. chongi was first determined by DNA sequencing based on the PCR fragments. The complete mitochondrial DNA (mtDNA) genome sequence of S. chongi is a circular molecule of 16, 584 bp in length. It consists of 13 protein-coding genes, 22 tRNA genes, 2 rRNA genes, and a control region (D-loop). The gene nucleotide composition of S. chongi is 29.6% A, 27.1% C, 17.9% G, and 25.4% T, with a high AT content (55.0%). The results could provide useful data for further studies on phylogenetics, conservation genetics and rational resource management for S. chongi .